Hypertension in Pregnancy Is a Risk Factor for Microalbuminuria Later in Life. Issue 9 (29th April 2013) - Kattah, Andrea G.; Asad, Reem; Scantlebury, Dawn C.; Bailey, Kent R.; Wiste, Heather J.; Hunt, Steven C.; Mosley, Thomas H.; Kardia, Sharon L. R.; Turner, Stephen T.; Garovic, Vesna D.
Abstract : The authors aimed to compare renal function by estimated glomerular filtration rate and albuminuria in 3 groups of women: nulliparous women, women with a history of normotensive pregnancies, and women with a history of at least one hypertensive pregnancy. Women who participated in the second Family Blood Pressure Program Study visit (2000–2004) and had serum creatinine and urine albumin measurements (n=3015) were categorized as having had no pregnancy lasting >6 months (n=341), having had only normotensive pregnancies (n=2199), or having had at least 1 pregnancy with hypertension (n=475) based on a standardized questionnaire. Women who reported having had at least one pregnancy with hypertension were significantly more likely to be hypertensive (75.6% vs 59.4%, P <.001), diabetic (34.2% vs 27.3%, P ≤.001), and have higher body mass index (32.8 vs 30.5, P <.001) than those who reported normotensive pregnancies. There was a significantly greater risk of microalbuminuria (urine albumin‐creatinine ratio >25 mg/g) in those who reported at least one pregnancy with hypertension (odds ratio, 1.37; confidence interval, 1.02–1.85; P =.04) than in those with normotensive pregnancies, after adjusting for risk factors for chronic kidney and cardiovascular disease. Hypertension in pregnancy is associated with an increased risk of future microalbuminuria.